1992
DOI: 10.1111/j.1399-6576.1992.tb03452.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anaesthesia and surgery on the immune response

Abstract: Alterations have been found to occur in every component of immune response during anaesthesia and surgery. These alterations represent the body's general physiological responses and are mainly dependent on the extent of surgery, as well as other factors such as the patient's age and health status, medication and blood transfusion. Anaesthetic and operative complications have profound effects on these responses. Basically, the immune response to anaesthesia and surgery is a beneficial reaction, needed in local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
2
16

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(196 citation statements)
references
References 261 publications
6
172
2
16
Order By: Relevance
“…Surgery may cause tumor cells to detach from primary tumors and disseminate throughout the body (van der Bij et al, 2008). Meanwhile, cell-mediated immunity is suppressed after surgery (Faist et al, 1986;Salo, 1992; Boomsma et al, Figure 3. Naringenin promotes T cell activation and restores T cell function in a tumor resection model.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery may cause tumor cells to detach from primary tumors and disseminate throughout the body (van der Bij et al, 2008). Meanwhile, cell-mediated immunity is suppressed after surgery (Faist et al, 1986;Salo, 1992; Boomsma et al, Figure 3. Naringenin promotes T cell activation and restores T cell function in a tumor resection model.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system and different cytokines could be influenced by surgery (Salo, 1992;Hensler et al, 1997). In previous studies, it has been shown that the increase in concentration of IL-6 correlates well with operating time, severity of sepsis, and clinical complications after surgery (Damas et al, 1992).…”
Section: Modulation Of Cytokine Production By Tramadolmentioning
confidence: 99%
“…Surgical trauma and anesthesia are associated with a complex dysregulation of the immune system and with the activation of both proinflammatory and anti-inflammatory responses (Salo, 1992). Interleukin-1 (IL-1), tumor necrosis factor-α (TNF-α) and IL-6 have local and systemic effects that may limit injury and the spread of infection and provide a suitable environment for tissue healing and repair (Sheeran and Hall, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Neuraxial anesthesia may decrease the risk of a surgical site infection via transfusion, which has been shown to be a risk factor for surgical site infections [24]. However, the lower risk of systemic infections after using neuraxial anesthesia cannot be fully explained by reduction in transfusions and might be related to changes in immune system response after general and neuraxial anesthesia [5,25,26]. Volk et al [26] suggested that neuraxial anesthesia preserves lymphocyte functions, which may contribute to ''infectious resistance'' after neuraxial anesthesia.…”
Section: Discussionmentioning
confidence: 99%